Urgensi Landasan Yuridis-Politis dalam Kebijakan Pendidikan di Indonesia - Bagus Rachmad Saputra; Darmaji Darmaji; Ahmad Supriyanto; Nurul Ulfatin (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The writing of this article aims to find out the juridical and political foundations in education, as the basis of the implementation and legitimacy of the implementation of the education policy itself. The juridical-political foundation becomes a strong legal basis in guiding the implementation of education in accordance with the mandate of the law to educate the life of the nation. The writing of this article uses a literature study approach which examines theories that are relevant to the juridical and political foundation in education and policy implementation at the level of the central government, regional government, to the education unit level. The writing of this article can be a reference for the implementation of learning in educational institutions related to educational policies that are based on juridical and political foundations.